2014
DOI: 10.1371/journal.pone.0085327
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Associated with Increased Risk of Non-Adherence to Antiretroviral Therapy among HIV-Infected Adults in the Democratic Republic of Congo: A Cross-Sectional Study

Abstract: BackgroundFood insecurity is increasingly reported as an important barrier of patient adherence to antiretroviral therapy (ART) in both resource-poor and rich settings. However, unlike in resource rich-settings, very few quantitative studies to date have investigated the association of food insecurity with patient adherence to ART in Sub-Saharan Africa. The current study examines the association between food insecurity and adherence to ART among HIV-infected adults in the Democratic Republic of Congo (DRC).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 54 publications
13
84
2
7
Order By: Relevance
“…Similar findings were made in Ethiopia where it was observed that unemployed patients were more likely to be depressed and less likely to socialize, leading to miss appointments and access to health care [23]. Similar findings were also made in Cameron where it was reported that adherence was high among employed patients as compared to unemployed patients [24]. Similar findings has been observed in low-income countries where it was found that overall pooled odds ratio (OR) for the association between being employed and adhering to ART was 1.85 [25].…”
Section: Influence Of Economic Factors On Art Adherencesupporting
confidence: 75%
“…Similar findings were made in Ethiopia where it was observed that unemployed patients were more likely to be depressed and less likely to socialize, leading to miss appointments and access to health care [23]. Similar findings were also made in Cameron where it was reported that adherence was high among employed patients as compared to unemployed patients [24]. Similar findings has been observed in low-income countries where it was found that overall pooled odds ratio (OR) for the association between being employed and adhering to ART was 1.85 [25].…”
Section: Influence Of Economic Factors On Art Adherencesupporting
confidence: 75%
“…This sample size was calculated to correctly assess the proportion of HIV-infected individuals with food insecurity, based on the national data in the DRC of 57% [18]. The power calculation used the Kish-Leslie formula, with a 5 % level of precision, a confidence interval (CI) of 95 %.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…A review of existing literature revealed that, unlike in resource-rich settings, limited data is available from validated measures of food insecurity that describe the association between food insecurity and nutritional status among patients on ART [17,18] in SSA. Especially the link between food insecurity and adherence to ART seems to relate to treatment failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study conducted in South Africa revealed that the physiological complications of progression of HIV infection and poverty were determinants of insufficient consumption of a diet of adequate quality and quantity to booster immune function and support medical therapy [28]. Studies conducted in different parts of Africa showed that HIV/AIDS depletes financial capital, social capital and human capital as labor is lost through decreased productivity and the death of the productive member of the family [29,30].…”
Section: Introductionmentioning
confidence: 99%